Key Competencies for Industrial Relations Managers : A Case Study from West Bengal - Das, Mukesh Ranjan; Pathak, Pramod; Das, Mohit Ranjan (Prabandhan: Indian Journal of Management, 2018)
Statistics have evidence that Industrial Relations disputes have reduced in our country from 3000 disputes in a year to 300 disputes in 2008. However, in recent times, there was a sudden surge in violent incidents at Pricol (2009), Allied Nippon (2010), Prowmex Steel (2011) in which senior officials like CEOs and HR officials were killed. The worst industrial violence in the country took place on July 18, 2012 at Suzuki’s plant at Manesar in which 100 supervisors and nine policemen were injured, and the General Manager (HR) was left in his chamber with broken arms and legs, and the room was set ablaze, leaving the GM to die ! It also resulted in a loss of ` 1500 crores. The most - recent incident being, a sacked employee along with an accomplice on bike opened fire and injured an HR Manager of Mitsubishi Corporation on June 7, 2018 while he was coming for duty by his car. These incidents highlight the fact that competencies for apt handling of industrial relations in the manufacturing industry are still a critical competency. This case study attempted to delineate the desired competencies for industrial relations managers through a real case of the year 2003 of one of the factories of a Fortune 500 PSU company situated in Durgapur, West Bengal. The state was then ruled by the CPM Govt. Unions were affiliated with the Communist Party of India, and strikes happened at the drop of a hat. The Central Govt. had already dismantled the administrative price mechanism in the petroleum industry to allow a level playing field for private investors like Reliance, Essar Shell, and Supergas. This warranted substantial reduction in labour (as they were in excess number) cost of existing PSU units to remain competitive. The case has two parts : Part-1 depicted the complexity of the IR situation in the factory, and Part - II narrated what was actually done in the same factory in order to bring the desired cost reduction against severest odds. The case delineated competencies like achievement orientation, integrity, persuasive ability, emotional competence as differentiating competencies for industrial relations practitioners.